Fiscal year 2003 : State homeland security grant program, Part II : program guidelines and application kit (Washington, D.C. : U.S. Dept. of Homeland Security : Office for Domestic Preparedness, [2003], 2003)
1 volume (various pagings) ; 28 cm
Cover title.;Shipping list no.: 2004-0059-P.;"SL00618.";Also available via Internet from the ODP Web site. Address as of 01/13/04: http://www.ojp.usdoj.gov/odp/docs/fy03shsgp2.pdf; current access is available via PURL.